PENGARUH KEPEMIMPINAN, LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. UNGARAN INDAH BUSANA (Students' Journal of Economic and Management, 2014)
The success of an organization is determined by a leader in implementing leadership and can synchronize their work environment and organizational culture that supports in a company. This study is a study that examines the effect of leadership, workplace environment and organizational culture on employee performance on PT.Ungaran Beautiful Clothing. There are several factors that affect performance, but in this study only use the factors of leadership, workplace environment and organizational culture although there are many other factors that support out there. In this study, researchers used simple random sampling and sample rate and gain 100 employees. Employee data is then tested using the KMO, Loading factor and multiple regression. The third variable is the result of leadership and no significant negative effect on performance, work environment and a significant positive effect on performance, and organizational culture is not significant and positive effect on performance, Adjusted R square value of 0.063. Show that leadership, workplace environment and organizational culture could only explain 6.3% of the employee's performance variables. While 93.7% of employee performance.Keywords: Leadership, Work Environment, Organizational Culture and Performance